The struggles of Ceylonese women in Rani Manickas, the rice mother and the Japanese lover - Mani, Manimangai (IFERP, 2016)
The Ceylonese Tamils migration to Malaya started after the year 1894. Most of them were educated and were employed in the British civil service in Malaya. Brides were often imported from Ceylon for these men who are well settled in this new country. This study intends to expose the struggles faced by these Ceylonese Tamil women who were displaced due to marriage in the pre-colonial Malaya. The struggles of these women will be based on the female characters in Rani Manickas, The Rice Mother (2002)and The Japanese Lover (2010). Manicka, who is of Sri Lankan origin, was born and educated in Malaysia. She sheds light on the complications and challenges faced by displaced women in a patriarchal society and the roles they are expected to play. Both the novels selected for this study depict the journey of imported brides in Malaya and the difficulties faced by them in adapting to the new environment. These two novels will be studied in the light of postcolonial theory by looking into the issues of displacement and identity. This paper will reveal the difficulties faced by these women in adapting to the new place and culture. Secondly, it will explore the hardships faced by these women during the Japanese occupation and finally the roles that were destined to be played by these women. Being displaced in a strange land, the main characters in both novels are forced to adapt to the new environment and the new roles that the society expected them to play..